Nanostructure and mechanical behavior of metastable Cu–Cr thin films grown by molecular beam epitaxy. (15th January 2015) - Harzer, T.P.; Djaziri, S.; Raghavan, R.; Dehm, G.
Abstract: Metastable binary Cu–Cr alloys with nominal film thicknesses of 300 nm and chemical compositions in the range of 4–93 at.% Cr were synthesized via co-evaporation using molecular beam epitaxy. All films were grown onto Si (1 0 0) substrates at deposition rates of ∼0.05 nm s −1 . The film microstructures were studied by using transmission electron microscopy and X-ray diffraction. The mechanical properties were investigated by the nanoindentation technique. Depending on the chemical composition, three types of thin film microstructures are observed, which all exhibit tensile residual stresses. For a Cr concentration of 4 at.% a single-phase face-centered cubic (fcc) film was formed, whereas single-phase body-centered cubic (bcc) films were observed for Cr concentrations ⩾ 33 at.%. In the case of a Cu85 Cr15 film, a two-phase fcc and bcc structure is formed. An increase of the atomic fraction of Cr induces a significant refinement of grain sizes, from ∼100 nm for a Cu96 Cr4 alloy to ∼30 nm in the case of a Cu20 Cr80 alloy. Consequently, the hardness of the alloy films increased from 5.5 to 11.8 GPa. In addition, the formation of supersaturated solid solutions of Cr in single-phase fcc Cu films and Cu in single-phase bcc films was observed. Predictions of existing models of solid solution and grain boundary strengthening were evaluated and correlated with the mechanical properties of the films with respect to film compositions and grain sizes.